The gender gap on public opinion towards genetically modified foods. Issue 4 (1st December 2018) - Elder, Laurel; Greene, Steven; Lizotte, Mary Kate
Abstract: Ever since genetically modified (GM) foods were introduced into the food supply in the 1990s they have provoked debate and concern. The number of GM foods approved by the U.S. Food and Drug Administration and offered on supermarket shelves has steadily grown at the same time that public wariness about the safety of GM foods has increased. Studies within the scientific literature show a strikingly large gender gap in attitudes towards GM foods with women consistently more skeptical than men. However, there have been few efforts to understand the determinants of the gender gap on GM foods within the political science literature. This study employs a 2014 Pew Research Center survey on science issues to test several possible explanations for the gender gap in attitudes towards GM foods rooted in the different life experiences of women and men. The results show that while being a parent predicts more skeptical views about genetically modified foods overall it does not explain the gender gap in attitudes. In contrast, knowledge about science and having confidence in science do play a significant role in mediating the gender gap. By exploring the robust and pervasive gender gap on the issue of GM foods, this study sheds light on the fundamentally different ways men and women approach political issues.